Comprehensive RNA-Seq Analysis on the Regulation of Tomato Ripening by Exogenous Auxin. - Jiayin Li; Xiaoya Tao; Li Li; Linchun Mao; Zisheng Luo; Zia Ullah Khan; Tiejin Ying (PLoS ONE, 2016)
Auxin has been shown to modulate the fruit ripening process. However, the molecular mechanisms underlying auxin regulation of fruit ripening are still not clear. Illumina RNA sequencing was performed on mature green cherry tomato fruit 1 and 7 days after auxin treatment, with untreated fruit as a control. The results showed that exogenous auxin maintained system 1 ethylene synthesis and delayed the onset of system 2 ethylene synthesis and the ripening process. At the molecular level, genes associated with stress resistance were significantly up-regulated, but genes related to carotenoid metabolism, cell degradation and energy metabolism were strongly down-regulated by exogenous auxin. Furthermore, genes encoding DNA demethylases were inhibited by auxin, whereas genes encoding cytosine-5 DNA methyltransferases were induced, which contributed to the maintenance of high methylation levels in the nucleus and thus inhibited the ripening process. Additionally, exogenous auxin altered the expression patterns of ethylene and auxin signaling-related genes that were induced or repressed in the normal ripening process, suggesting significant crosstalk between these two hormones during tomato ripening. The present work is the first comprehensive transcriptome analysis of auxin-treated tomato fruit during ripening. Our results provide comprehensive insights into the effects of auxin on the tomato ripening process and the mechanism of crosstalk between auxin and ethylene.